Antimicrobial Stewardship in Saudi Arabia: A Narrative Review of Insights from Physicians, Pharmacists, and Nurses - Alomair, Bander Ibrahim; Aldhafeeri, Mutlaq Khelaif; Almutairi, Mohammed Abdullah; Alshammari, Fahhad Mashal; Alharbi, Abdullah Athal; Almotiry, Obied Mathil; Dighriri, Ibrahim Mohammed; Alharthi, Mohammed Saed Mohammed; Almalki, Abdulmajeed Ali; Alwathnani, Mokhlid; Almansour, Ali Mohammed Mabkhout; Alkulaib, Hamad Duhayan Ali; et al. (Journal of Ecohumanism, 2024)
Antimicrobial resistance (AMR) is a serious public health challenge fueled by the misuse and overuse of antibiotics. Antimicrobial stewardship (AMS) programs are central to the proper use of antimicrobials, patient outcomes improvement, and resistance reduction. Over the years, AMS has taken top place in Saudi Arabia as part of its healthcare reform. Therefore, the present narrative review aims to summarize the opinions of physicians, pharmacists, and nurses regarding the current practices of AMS in Saudi Arabia. It discusses the successes, challenges, and importance of interprofessional collaboration in Saudi Arabia. Significant barriers include insufficient infrastructure and training, cultural factors influencing prescription practices, and relatively low penetration into decision-making roles. Successes include adopting explicit AMS policies, increasing awareness among healthcare professionals regarding AMS issues, and several ongoing training programs. Recommendations for AMS improvement consist of furthering interprofessional collaboration, building educational efforts, implementing advanced diagnostics, raising the level of authority of pharmacists and nurses, and investing in health infrastructure for better real-time surveillance and support for evidence-based prescribing.